The extent to which some of the TQM standards are applied in the faculties of Khartoum State University and Sudan Private International University - Suleiman, Amani Suleiman Ahmed (Journal of Economic, Administrative and Legal Sciences, 2019)
The objective of the study was to investigate the extent to which some of the TQM standards were applied in the faculties of Khartoum State University and Sudan International Private University from the point of view of the faculty and the effect of the variables (age, gender, academic qualifications, years of experience, On the answers of the sample, and used the descriptive statistical method. The study was carried out with the following results: The application of TQM in some of the faculties of Khartoum State University and Sudan University of the World (3.46) with a total average of (3.46 of 5) with (large) estimates. According to the fields, the field of quality requirements in education has a general average of (3.84) with a large estimate; followed by the follow- Thirdly, the field of human resources development was average (3.37), and lastly, Decision-making and community service an average of (3.03), all of which estimates (medium). The results of the study showed that there are no differences in the application of some TQM standards in Sudanese higher education institutions due to variables (years of experience, age, scientific qualification and gender). In light of the results of the study, a number of recommendations were made to increase awareness and activate the implementation of some of the TQM standards in Khartoum State University Colleges, Sudan Private International University and all Sudanese higher education institutions. And attention to the educational environment within the university and methods of communication and communication. And to spread the culture of quality to managers and deans first to convince them of the importance of change and improve the performance and the importance of quality standards in institutions of public and private higher education as well as higher institutes